Mentoring as a Strategic Approach in Preparing Business Plans for Young Start-ups: A Case Study of Thai Snack MSMEs - Syafei, M. Yani; Thapjun, Aujchara; Vorachat, Chonchanok; Wiryo, Purwadhi Sawal; Rohendi, Acep; Handayani, Nining; Sutisnawati, Yayah; Fitra, Eldeast Jane Abdul (International Journal of Community Service (IJCS), 2025)
The ability to design a structured and feasible business plan is one of the critical factors for the sustainability of start-ups, especially those run by young entrepreneurs with limited managerial experience. This study aims to explore the role of mentoring in assisting young start-ups in preparing comprehensive business plans, with a case study on a micro, small, and medium enterprise (MSME) producing Thai snack products. Using a qualitative approach, data were collected through mentoring sessions, in-depth interviews, and observation of the business planning process. Improving entrepreneurs’ understanding of market analysis, financial projection, product positioning, and risk management. Moreover, mentoring enhances the confidence and strategic decision-making abilities of young business owners. The case study of the Thai snack MSME demonstrates that structured mentoring not only improves the quality of the business plan but also increases the potential for business growth and sustainability. This research contributes to the literature on entrepreneurship education and provides practical insights into how mentoring programs can be optimized to strengthen the competitiveness of young start-ups in the food industry.